Ankle Fracture and Length of Stay in US Adult Population Using Data From the National COVID Cohort Collaborative. Issue 1 (February 2022) - Pitts, Charles C.; Levitt, Eli B.; Patch, David A.; Mihas, Alexander K.; Terrero, Alfredo; Haendel, Melissa A.; Chute, Christopher G.; Ponce, Brent A.; Theiss, Steven M.; Spitler, Clay A.; Johnson, Michael D.
Background: The National COVID Cohort Collaborative (N3C) is an innovative approach to integrate real-world clinical observations into a harmonized database during the time of the COVID-19 pandemic when clinical research on ankle fracture surgery is otherwise mostly limited to expert opinion and research letters. The purpose of this manuscript is to introduce the largest cohort of US ankle fracture surgery patients to date with a comparison between lab-confirmed COVID-19–positive and COVID-19–negative. Methods: A retrospective cohort of adults with ankle fracture surgery using data from the N3C database with patients undergoing surgery between March 2020 and June 2021. The database is an NIH-funded platform through which the harmonized clinical data from 46 sites is stored. Patient characteristics included body mass index, Charlson Comorbidity Index, and smoking status. Outcomes included 30-day mortality, overall mortality, surgical site infection (SSI), deep SSI, acute kidney injury, pulmonary embolism, deep vein thrombosis, sepsis, time to surgery, and length of stay. COVID-19–positive patients were compared to COVID-19–negative controls to investigate perioperative outcomes during the pandemic. Results: A total population of 8.4 million patient records was queried, identifying 4735 adults with ankle fracture surgery. The COVID-19–positive group (n=158, 3.3%) had significantly longer times to surgery (6.5 ± 6.6 vs 5.1 ± 5.5 days, P = .001) and longer lengths of stay (8.3 ± 23.5 vs 4.3 ± 7.4 days, P < .001), compared to the COVID-19–negative group. The COVID-19–positive group also had a higher rate of 30-day mortality. Conclusion: Patients with ankle fracture surgery had longer time to surgery and prolonged hospitalizations in COVID-19–positive patients compared to those who tested negative (average delay was about 1 day and increased length of hospitalization was about 4 days). Few perioperative events were observed in either group. Overall, the risks associated with COVID-19 were measurable but not substantial. Level of Evidence : Level III, retrospective cohort study.